Attitude Towards Online Education During Covid-19 Pandemic Among Bachelor Level Students of Jumla - Lama, Monika; Ojha, Sujata; Rai, Maya; K.C. , Reshma; Neupane, Pratima; Shrestha, Pragya; Panta, Prem Prasad; Maharjan, Ramu; K.C., Shreejana (Journal of Karnali Academy of Health Sciences, 2023)
Background: Health science students, since long time, have been using digital technology mainly for the research purposes only. Due to global spread of corona virus disease (COVID-19), education system has changed and adopted online education which was a solution for the continuity of teaching and learning process during COVID-19 pandemic. The main objective of this study was to assess the attitude towards online education among bachelor level health science students. Methods: A descriptive cross-sectional study was carried out at Karnali Academy of Health Sciences, Jumla. Complete enumeration was done. Total 68 bachelor level students were taken for the study. A pretested self administered questionnaire was used for data collection. Data were entered and analyzed by using SPSS version 16. Frequency and percentage were also computed for demographics variables. Chi-square test was applied to assess the association between socio-demographic variables and attitude level. Results: The study illustrated that, among the 68 bachelor level students, nearly two third (63.2%) students had negative attitude towards online education during COVID-19 pandemic. There was statistically significant association of attitude level with ethnicity, type of program and strength of internet connection (p≤0.05). Conclusion: Majority of students of Karnali Academy had negative attitude towards online education; and they had faced many difficulties like internet and electricity problem etc. Administration and faculty members should take necessary measures for improving online education.